Mechanically tough and recoverable hydrogels via dual physical crosslinkings. Issue 19 (1st October 2018) - Yang, Fengyu; Ren, Baiping; Cai, Yongqing; Tang, Jianxin; Li, Ding; Wang, Ting; Feng, Zhangqi; Chang, Yung; Xu, Lijian; Zheng, Jie
ABSTRACT: Development of functional tough hydrogels with new network structures and energy dissipation mechanisms has great promise for many applications. Here, a new type of physical hydrogel crosslinked by hydrophobic association and hydrogen bonds was synthesized by a facile micellar copolymerization of hydrophobic methyl acrylate (MA) monomers and hydrophilic N‐hydroxyethyl acrylamide (HEAA) monomers in the presence of Tween80 micelles. Strong hydrophobic association between inner MA and Tween80 and hydrogen bonds between external polyHEAA and Tween80 provide two distinct crosslinkers to construct mechanically tough and recoverable network. Mechanical properties of polyHEAA‐MA@Tween80 hydrogels strongly depended on network components (HEAA, MA; Tween80 concentrations). At optimal conditions, the hydrogels can achieve fracture stress of 700 kPa, fracture strain of 1687 mm/mm, elastic modulus of 195 kPa, and tearing energy of 1598 J/m 2 . Due to the reversible nature of physical interactions, polyHEAA‐MA@Tween80 hydrogels can achieve fast stiffness/toughness recovery of 60%/33% without any external stimuli and resting time at room temperature. This work demonstrates a new design strategy to fabricate a new a single‐network hydrogel with high mechanical and self‐recovery properties by incorporating both hydrophobic association and hydrogen bonds in the network, which may provide alternative viewpoint for the design of multifunctional tough hydrogels. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2018, 56, 1294–1305 Abstract : A new type of physical hydrogel of polyHEAA‐MA@Tween80 is developed by incorporating both hydrophobic association and hydrogen bonds in the network in the presence of Tween80 micelles. Strong hydrophobic association between inner MA and Tween80 and hydrogen bonds between external polyHEAA and Tween80 provide two distinct crosslinkers to construct a mechanically tough and recoverable network without any external stimuli, which may provide an alternative viewpoint for the design of multifunctional tough hydrogels.